Magnolia x soulangiana 'Picture' 'Picture' Saucer Magnolia: FPS-372/FP372, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of the ‘Picture’ saucer magnolia (Magnolia x soulangiana ‘Picture’). It describes the plant’s growth habits, blooming period, and physical characteristics, including its large, pink and white flowers. The document also covers the plant’s preferred growing conditions, such as soil type, light requirements, and hardiness zones. Additionally, it highlights the plant’s uses in landscaping, its moderate drought tolerance, and its general pest resistance. The document emphasizes the importance of early training to develop the desired form and notes potential issues like frost damage and canker diseases. Original publication date October 1999.